Women's relationships in classical Attika - Backler, K (2021)
This thesis offers a new assessment of the relationships of fifth- and fourth-century Attic women, of citizen and metic status. Chapter 1 demonstrates women’s capacity to build and use relationships through and against the vicissitudes of their lives, particularly their transitions between marriages and households. Chapter 2 argues for women’s ability to shape formal and informal kinship structures in response to their own affective relationships. Chapter 3 suggests that women could use their relationships with enslaved people, particularly enslaved women, either to confirm or challenge their other roles and relationships within the household. Chapter 4 shows how income-generating work expanded women’s social networks, gave them opportunities publicly to present themselves in terms and contexts independent of their family relationships, and enabled them to redefine their roles within their families. Chapter 5 shows how women formed, used, and defined their friendships, considering in particular the role of the neighbourhood and of religion as contexts within which women could shape their social landscapes.